Unruly equality U.S. anarchism in the twentieth century - Cornell, Andrew 1977- (University of California Press, 2016)
"In this highly accessible social and intellectual history of American anarchism in the United States, Andrew Cornell reveals an amazing continuity and development across the twentieth century. Far from fading away, anarchists dealt with major events such as the rise of Communism, the New Deal, atomic warfare, the black freedom struggle, and a succession of artistic avant-gardes stretching from 1915 to 1975. This book traces U.S. anarchism as it evolved from the creed of poor immigrants militantly opposed to capitalism early in the twentieth century to one that today sees resurgent appeal among middle-class youth and foregrounds ecology, feminism, and opposition to cultural alienation"...Provided by publisher